Desain Bahan Ajar Analisis Real dengan Taksonomi Solo Dilengkapi Soal-Soal Bentuk Superitem - Firmasari, Siska; Pramuditya, Surya Amami (Universitas Hamzanwadi, 2018)
Real Analysis is a compulsory subject for the 3rd grade students of Mathematics Education that most of students Â are considered it as a difficult course, due to the abstract of material especially on the matter of the Real Numbers. The purpose of this research is to design learning materials with SOLO taxonomy completed with such a multilevel exercise form super item to obtain a valid learning materials and practical to address the difficulties of students in learning the material of Number Real. This research uses research methods of modified Plomp. The referred design in this research is the design of learning materials. The results show that 1) The material design includes in valid criteria, based on the average value of validation materials of 4.52; 2) The practicality of material design is gained from the results of students positive response that is Â 91.96% and a good ability of the lecturer in teaching using materials that have been compiled.